Modeling of p-aminophenol compounds as analgesic antiinflammatory based on biologic activity and structure relationship - ., Pudjono; Susilowati, Sri Sutji; ., Rehana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
This research aim was to find out the new compounds model of paminophenol derivates which have analgesic anti-inflammatory activity based on structure and biologic activity relationship analysis by computation methods. Seventeen compounds of p-aminophenol derivates were used in this research, and six compounds known its analgesic-antiinflammatory activity were used for determine QSAR equation model. This research’s result was a QSAR equation that can be using for synthesis the higher activity new compound of paminophenol. Key words : p-aminophenol compounds, analgesic anti-inflammatory activity, structure and activity relationship, QSAR equation, computation methods